Development of Ethnoscience-Based Teaching Materials in Class V Elementari School - Liza Ayu Anggriani; Hasnawati Hasnawati; Nurhasanah Nurhasanah (Yayasan Insan Mulia Bima, 2024)
Ethnoscience-based learning in science learning it is very important for students to learn science contextually and be able to implement their knowledge in real life. This research aims to produce ethnoscience-based teaching materials to support the science learning process regarding material components (substances) in class V at Elementary School that are valid and practical. This research is a type of Research and Development (R&D) research using the 4D development model (Define, Design, Development, and Disseminate). The place where the research was conducted was at Elementary School. The subjects of this research were 7 class V students at Elementary School. Meanwhile, the object of this research is ethnoscience-based teaching materials regarding the components of material preparation (substances). The research instruments used were media and material expert validation questionnaires as well as teacher and student response questionnaires. The results of this research show that ethnoscience-based teaching materials to support the science learning process, material about the components that make up material (substances) received a percentage of 95.33% with very valid criteria from media experts, a percentage of 96.66% with very valid criteria from material experts, percentage 95.5% with very practical criteria from teacher responses, a percentage of 86% with very practical criteria from student responses. Therefore, it can be concluded based on the research results that ethnoscience-based teaching materials, materials about the components that make up the material (substances) can be declared valid and practical to support the science learning process in class V at Elementary School.